A visual and creative approach to exploring people with dementia's experiences of being students at a school in Denmark. (April 2020) - Ward, Alison; Schack Thoft, Diana; Lomax, Helen; Parkes, Jacqueline
In dementia research, there is limited knowledge about how people with dementia experience their daily life including how they experience the services they attend. This means a lack of knowledge about how people with dementia judge the quality of services provided for them. In this study visual and creative methods were used to understand the experience of people with early stage dementia who attend an adult school, Voksenskolen for Undervisning og Kommunikation (VUK) in Denmark. The study explored the students' experience of being a student at VUK and what it means to engage in life-long learning. Alongside the aim to evaluate the service provided for them, seen from their perspective. Photo-elicitation was used, with cameras provided to each student, who took photographs of their school and home life. Students' photographs were used to support focus group discussions, with the images integral to the process of talking about and recalling stories. Ten students were recruited to participate in four weekly sessions. Two groups were run with five students in each group. Each session was video recorded, these sessions were then transcribed and analysed using Braun and Clarke's thematic analysis. Visual images were found to support the students' memory of current experiences and prompted reminiscences about the past, leading to rich descriptions about being a student at VUK and their experiences of living with dementia. Being able to attend VUK was found to be important for these students with dementia, providing them with a sense of purpose, a way to support their cognitive function and also to develop new friendships. The method provided a way for people with dementia to be active in the research process and provide their perspective about a novel service, which promotes an ethos of learning and development.